Brunelli (Dorsoulnar) Flap for the Reconstruction of Defect of the Thumb Nail Unit After Oncological Resections With Mohs Micrographic Surgery - Felipe Mesa, MD, PhD; Oscar Leal, MD; María Elena Ramos, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The Brunelli flap is an option in the reconstruction of the thumb after trauma or oncological resections. The arc of movement of the flap makes it possible to resolve defects in the proximal, palmar, dorsal, and lateral regions. Methods:. We present a case series of 11 patients in whom a Brunelli flap was performed for postoncological reconstruction, melanoma in situ, and invasive squamous cell carcinoma of the thumb nail unit associated with Mohs micrographic surgery. This combination has not been described before. Results:. The reconstruction was carried out using a Brunelli flap, incorporating certain variations to the original technique. Clinical follow-up was performed during a 1-year period. All flaps showed good viability. In 3 flaps, there was mild distal suffering that resolved with local healing. Three patients presented hypersensitivity in the distal part, which was managed with physical therapy. The functionality of the thumb was not altered in any case, and there were no complications in the donor site. No tumor recurrence was documented in any patient. Conclusions:. The use of the Brunelli flap to reconstruct the nail unit after an oncological resection with Mohs surgery is a good alternative. The advantages include a dorsal artery as a constant vessel and a homodigital flap that does not cause morbidity in the donor area, and with Mohs surgery, amputation is avoided. Disadvantages include lack of sensation of the flap. Some limitations of our study are the sample size and lack of long-term follow-up.